Association between hemoglobin-to-red blood cell distribution width ratio and rheumatoid arthritis in US adults: evidence from the national health and nutrition examination survey 2009–2018 - Nian Kuang; Jing Liu; Zhaoduan Hu; Yanxia Wu; Rui Peng (Preventive Medicine Reports, 2025)
Objective: This cross-sectional study aimed to investigate the association between the hemoglobin-to-red blood cell distribution width ratio (HRR) and rheumatoid arthritis in adults. Methods: Cross-sectional data from 22,352 participants in the National Health and Nutrition Examination Survey (NHANES) 2009–2018 were analyzed. HRR was defined as hemoglobin concentration (g/dL) divided by red blood cell distribution width (%) and grouped into quartiles. The multivariable logistic regression model and restricted cubic spline (RCS) models assessed the connection between HRR and rheumatoid arthritis, adjusted for demographics, socioeconomic factors, and comorbidities. Results: Our findings reveal a significant negative correlation between HRR measurements and rheumatoid arthritis susceptibility. Higher HRR quartiles showed progressively lower rheumatoid arthritis risk (quartile 4 vs. quartile 1: OR = 0.68, 95 % CI: 0.56,0.83). RCS revealed an inverse linear association after adjustment (P for overall <0.001; P for nonlinear = 0.174). Conclusions: HRR is inversely associated with rheumatoid arthritis risk, suggesting its potential as a biomarker for rheumatoid arthritis risk stratification. Nevertheless, additional investigations are required to corroborate these observations.